Surgical management of mitral annular calcification. (March 2020) - El-Eshmawi, Ahmed; Alexis, Sophia L.; Sengupta, Aditya; Pandis, Dimosthenis; Rimsukcharoenchai, Chartaroon; Adams, David H.; Tang, Gilbert H.L.
Abstract : Purpose of review: The aim of the article is to discuss different therapeutic options for patients with severe mitral valve dysfunction because of mitral annular calcification (MAC), including mitral valve repair, conventional mitral valve replacement, percutaneous transcatheter mitral valve replacement (TMVR), and hybrid procedures. Recent findings: Optimal management of severe mitral valve disease because of MAC remains challenging. Various 'resect' or 'respect' repair strategies have been standardized and are applicable in eligible patients. Mitral valve replacement with a standard surgical bioprosthesis is often possible in nonrepair candidates, especially with noncircumferential MAC. TMVR has evolved as a feasible option for anatomically and/or clinically prohibitive open-surgery cases, with the caveat of strict anatomic eligibility criteria. Hybrid TMVR provides the advantages of both open-surgery and TMVR and has emerged as a promising alternative in select patients. Summary: Surgical management of MAC and severe mitral valve disease continues to evolve. The addition of transcatheter valve options may benefit many patients previously considered inoperable and are now candidates for intervention. This review will summarize state-of-the-art management options for patients with MAC.